Exploring The Efficacy of Drill and Practice Methods in Improving Student Engagement and Learning Outcomes on The Salt Hydrolysis Topic - Fahmina, Shifi Syarifa; Susanti VH, Elfi; Ayni, Ayni (PAEDAGOGIA, 2023)
Effective teaching and improved learning outcomes rely on student engagement and active learning. Interactive, hands-on approaches are particularly valuable in science education for fostering better comprehension of scientific concepts. This research investigates the efficacy of the drill and practice method to enhance student engagement and learning outcomes in salt hydrolysis. The study follows a classroom action research design across two cycles in a public high school in Sukoharjo Regency, Indonesia. Participants were selected purposively due to identified issues in engagement and academic performance. Data collected via cognitive tests, observations, and questionnaires were analyzed descriptively. Results show that implementing the drill and practice method significantly heightened student engagement in salt hydrolysis, with active student percentage rising from 73% (Cycle I) to 88% (Cycle II). Cognitive learning outcomes also improved, progressing from 67% (Cycle I) to 81% (Cycle II). These findings hold significance for science education. The drill and practice approach enhances engagement and understanding, allowing educators to elevate learning outcomes. This method can cultivate engagement and boost learning in similar contexts, such as high school. By embracing interactive strategies, educators foster active participation, aiding students in mastering scientific concepts and addressing engagement and performance concerns